Teachers and teacher education in uncertain times. - O'Doherty, Teresa; Madalińska-Michalak, Joanna; Assunção Flores, Maria (Routledge, 2018)
EDITORIAL: Drawing on a range of international research perspectives, this Special Issue focuses on new insights into the challenges facing teachers, teacher educators and teacher education in uncertain times. Teachers and teacher educators, like the whole education system, have to response to the growing complexity of the challenges that are encountered in the contemporary world. These challenges range from the technological revolution, which is now part of everyday life, to the explosion of the knowledge economy, political instability in many regions, significant changes in migration patterns and the growth of refugee camps, to the rise in terrorism and violence in society.
Keywords: teachers; teacher educators; migration; multi-culturalism; educational reform